Dimethyl fumarate up-regulates expression of major neurotrophic factors in the epidermal neural crest stem cells. (February 2019) - Salehi, Mohammad Saied; Borhani-Haghighi, Afshin; Pandamooz, Sareh; Safari, Anahid; Dargahi, Leila; Dianatpour, Mehdi; Tanideh, Nader
Abstract: There is an agreement that combining treatments can lead to substantial improvement, therefore the present study assessed the effects of different concentrations of dimethyl fumarate (DMF) on viability of epidermal neural crest stem cells (EPI-NCSCs). In addition, this investigation was designed to evaluate the effects of DMF on relative expression of major trophic factors mainly the ones with neurotrophic effects, expressed in EPI-NCSCs in order to enhance their therapeutic potential. To determine the appropriate concentration of DMF for EPI-NCSCs treatment, the MTT assay was employed and based on the obtained data, EPI-NCSCs treated with 10μM DMF for 6, 24, 72 or 168 h. In each time point, quantitative RT-PCR technique was used to evaluate NGF, NT-3, BDNF, GDNF and VEGF transcripts. The acquired data showed that 10μM DMF significantly increased the mRNA expression of NGF, NT-3 and BDNF, 72 h following treatment; however, DMF inhibitory effect on GDNF mRNA expression was observed in various time points. No significant changes were detected for VEGF transcript. Our findings reveled that expression of major neurotrophic factors were up-regulated by dimethyl fumarate treatment. Therefore, combining EPI-NCSCs with DMF treatment might be a valuable strategy to improve their therapeutic functions in vivo .